JURIDICAL REVIEW OF INCENSION/BREATING RIGHTS TROUBLE World 2014 (Study of Supreme Court Decision Number 2/PDT.SUS-HKI/2018/ PN.Smg) - Ronald Hasudungan Sianturi; Geby Evanda; Dennis Satria A. Nainggolan (Awang Long Law Review, 2022)
PT. Inter Sport Marketing (PT. ISM) is one of the license holders from FIFA to serve the broadcast of the World Cup throughout the territory of the Unitary State of the Republic of Indonesia which has been created and signed by l ui license agreement dated May 5 , 2011 between PT. ISM with FIFA. The license agreement made PT. ISM becomes the Master Rights Holder for media rights . However, there are pros and cons which are two main issues . PT. ISM is a company domiciled in Indonesia and is one of the recipients of a license or has received official permission from FIFA to broadcast World Cup broadcasts throughout the territory of the Republic of Indonesia, has been made and signed me l a l ui l icence agreement dated 5 May 2011 between PT. ISM with FIFA. Legal position of PT. ISM as the holder of the copyright license and the legal consequences of the license agreement between the parties PT. ISM and FIFA against third parties; This research includes normative law with a conceptual approach based on legislation, doctrine, and jurisprudence, with the method of collecting data from library research; The result of this research concludes that PT . ISM has the legal standing or legal capacity to prohibit anyone or any party that harms rights throughout the commercial territory of the Republic of Indonesia . Under the FIFA license agreement is known to be valid, the license agreement has legal consequences for third parties which are defined as parties outside the above agreement.